Evaluation of Camel Well-being: Pathological Characteristics and Detection for Diseases - Adlin Jebakumari S, Dhananjay Kumar Yadav, Digvijay Singh (Revista Electronica de Veterinaria, 2024)
Camels play a crucial role in supporting livelihoods, transportation, and nourishment in many regions worldwide. Ensuring their well-being is vital for preserving natural equilibrium and supporting communities that depend on them. This study investigates the pathological features of tuberculosis (TB) in chronically infected dromedary camels raised on a well-managed ranch in India. The objective is to gain insights into the illness’s pathological components and evaluate the efficacy of various diagnostic procedures in identifying the illness. A collection of 120 dromedary camels from the organized farm was examined, with an emphasis on post-mortem examinations. Clinical symptoms and lesions in infected camels were analyzed in this study by means of in-depth clinical observations and pathological examinations. Furthermore, other diagnostic procedures were employed to evaluate their efficacy in TB detection, such as the 65-kilodalton heat shock protein (hsp65)Polymerase Chain Reaction (PCR), Acid-Fast Staining Stain (AFS), and Mantoux Test (MT). During the research period, 24 of the 120 camels evaluated had gross lesions suggestive of tuberculosis. There were two types of lesions in the afflicted camels: Reciprocity (n=18) and dissemination (n=6). Histopathological examination revealed typical Nodular Inflammatory Formations (NFM) lesions, with large cells and acid-fast microorganisms (AFM) occasionally observed in the Reciprocity version and frequently observed in the dissemination form. The diagnostic tests produced variable findings, with the MT discovering TB in 13 camels, the AFS showing TB in 15 camels, and the hsp65 PCR revealing TB in 24 infected camels. The study suggests that the Reciprocity type of tuberculosis is more widespread in camels, suggesting that the respiratory route is an important route of exposure in camel populations.